2012
DOI: 10.1590/s2237-93632012000300010
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of patients with ulcerative colitis from an university hospital at Natal, Brazil

Abstract: Introduction: Ulcerative colitis (UC) is a chronic inflammatory disease that affects the rectum and colon, involving periods of exacerbation and remission. A considerable number of patients requires surgery during the course of this disease. Objective: The purpose of this study is to analyze the profile and therapeutic approach of patients with UC. Methods: This is a retrospective study that analyzed medical records of patients diagnosed with UC between 1999 and 2010. We selected 45 patients and analyzed the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Late pouch-related complications following proctocolectomy and IPAA include pouchitis (in about a third of patients), pouch-vaginal fistula, and later pouch dysfunction due to pouch sepsis and pouchitis. 11,22,25 Late complications were present in 16% of the patients in this series. Three per cent of our patients with UC developed colorectal cancer, which falls within the 2-27% reported in international studies.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Late pouch-related complications following proctocolectomy and IPAA include pouchitis (in about a third of patients), pouch-vaginal fistula, and later pouch dysfunction due to pouch sepsis and pouchitis. 11,22,25 Late complications were present in 16% of the patients in this series. Three per cent of our patients with UC developed colorectal cancer, which falls within the 2-27% reported in international studies.…”
Section: Discussionmentioning
confidence: 72%
“…20 The EIMs were seen in 17% of CD patients in this series compared to the 40% reported in the literature 20 and in 16% of UC patients, which is higher than the 4.5-8% seen in certain Asian studies, 21 but lower than the 30-45% reported in the Western literature. 1,21,22 We concede that this is a select group of patients and this observation cannot be generalised to all patients with IBD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation